Two and Three-Dimensional Echocardiography in Primary Mitral Regurgitation: Practical Hints to Optimize the Surgical Planning - Pastore, Maria Concetta; Mandoli, Giulia Elena; Sannino, Anna; Dokollari, Aleksander; Bisleri, Gianluigi; D'Ascenzi, Flavio; Cavigli, Luna; Pasquini, Annalisa; Lisi, Matteo; Ghionzoli, Nicolò; Santoro, Ciro; Miglioranza, Marcelo Haertel; et al. (Frontiers in Cardiovascular Medicine, 2021)
Primary mitral regurgitation (MR) is the second most common valvular disease, characterized by a high burden in terms of quality of life, morbidity and mortality. Surgical treatment is considered the best therapeutic strategy for patients with severe MR, especially if they are symptomatic. However, pre-operative echocardiographic evaluation is an essential step not only for surgical candidate selection but also to avoid post-operative complications. Therefore, a strong collaboration between cardiologists and cardiac surgeons is fundamental in this setting. A meticulous pre-operative echocardiographic exam, both with transthoracic or transesophageal echocardiography, followed by a precise report containing anatomical information and parameters should always be performed to optimize surgical planning. Moreover, intraoperative transesophageal evaluation is often required by cardiac surgeons as it may offer additive important information with different hemodynamic conditions. Three-dimensional echocardiography has recently gained higher consideration and availability for the evaluation of MR, providing more insights into mitral valve geometry and MR mechanism. This review paper aims to realize a practical overview on the main use of basic and advanced echocardiography in MR surgical planning and to provide a precise checklist with reference parameters to follow when performing pre-operative echocardiographic exam, in order to aid cardiologists to provide a complete echocardiographic evaluation for MR operation planning from clinical and surgical point-of-view.